Teachers’ Views on Social Skills of Students with Special Needs in Inclusive Classrooms - Wahyuni, Sri; Reswita, Reswita; Fitriani, Dina (Gifted: Journal of Early Childhood Education, 2024)
This study explores teachers’ perceptions of the social skills of students with special needs within Indonesian inclusive school settings. Employing a qualitative case study approach, data were gathered through in-depth interviews and direct observations involving teachers who work directly with students with special needs. The findings indicate that while some progress is evident, students often exhibit underdeveloped social competencies—particularly in verbal communication, adherence to social norms, and peer interactions. Participants underscored the necessity of individualized strategies tailored to each student's unique developmental profile. This study offers a novel contribution by presenting firsthand insights from Indonesian teachers, highlighting context-specific challenges and practices in fostering the social development of students with special needs. The results aim to inform the design of inclusive learning programs that are more attuned to students’ social growth.